Peran Pengorganisasian Program Literasi Berbasis Masyarakat untuk Mendukung Pencapaian Sustainable Development Goals (SDGs) - Sahidi; Sri Wahyuni (Nur Science Institute, 2026)
The sustainability of community-based literacy programs is strongly influenced by the effectiveness of organizational management, particularly the implementation of the organizing function. This study aims to analyze the role of the organizing function in sustaining community-based literacy programs at Rumah Pintar Punggur Cerdas, Kubu Raya Regency, and its contribution to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 10 (Reduced Inequalities), and SDG 17 (Partnerships for the Goals). The study employed a qualitative approach using a case study design. Informants were selected through purposive sampling, while data were collected through in-depth interviews, observations, and document analysis. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings reveal that a clear division of responsibilities, a formal organizational structure, delegated authority, and continuous volunteer capacity development constitute the primary factors supporting the sustainability of the literacy program. Nevertheless, the limited number of permanent volunteers, reliance on internship students, and inadequate learning facilities remain significant challenges that require attention. The study concludes that the organizing function serves as a fundamental pillar in establishing sustainable governance for community-based literacy programs while strengthening the contribution of community organizations to improving the quality of education, expanding equitable access to literacy services for all members of society, and fostering collaborative partnerships to support the achievement of the Sustainable Development Goals.